2017
DOI: 10.3390/ijms18112418
|View full text |Cite
|
Sign up to set email alerts
|

The Small Heat Shock Protein α-Crystallin B Shows Neuroprotective Properties in a Glaucoma Animal Model

Abstract: Glaucoma is a neurodegenerative disease that leads to irreversible retinal ganglion cell (RGC) loss and is one of the main causes of blindness worldwide. The pathogenesis of glaucoma remains unclear, and novel approaches for neuroprotective treatments are urgently needed. Previous studies have revealed significant down-regulation of α-crystallin B as an initial reaction to elevated intraocular pressure (IOP), followed by a clear but delayed up-regulation, suggesting that this small heat-shock protein plays a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…On the other hand, a decrease of CRYAA has been associated with retinal dystrophy [52] and glaucomatous optic neuropathy [44]. However, intravitreal injection of CRYAB at the time of the intraocular pressure (IOP) increase rescued RGCs in a rat model of glaucoma [53]. The latter study also provided proteomic evidence that CRYAB injection upregulated all (α, β and γ) subclasses of crystallins in the retina, which induced the broad neuroprotective effects observed.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, a decrease of CRYAA has been associated with retinal dystrophy [52] and glaucomatous optic neuropathy [44]. However, intravitreal injection of CRYAB at the time of the intraocular pressure (IOP) increase rescued RGCs in a rat model of glaucoma [53]. The latter study also provided proteomic evidence that CRYAB injection upregulated all (α, β and γ) subclasses of crystallins in the retina, which induced the broad neuroprotective effects observed.…”
Section: Discussionmentioning
confidence: 93%
“…Retinal crystallins are also up-regulated in a variety of other retinal pathologies, including diabetic retinopathy, ischemia, mechanical injury and uveitis. The α-crystallin family plays a crucial role in neuroprotection and inflammation (Fort and Lampi, 2011), while the β-and γ-crystallins are small proteins with a possible ganglion cell protective role in glaucoma (Anders et al, 2017) and a role in retinal tissue remodeling and repair (Thanos et al, 2014). Consequently, the presence of these proteins in drusen points to a local cellular origin.…”
Section: Biological or Disease Motifs And Canonical Pathwaysmentioning
confidence: 99%
“…In contrast, overactive HSF1 is involved in cancer by promoting cancer cell adaptation and survival in stressful conditions 5. It has been found that HSPs, including Hsp70, α-crystallins, Hsp40, and Hsp110, were able to enhance the survival of retinal neurons in models of glaucoma,8,9 optic nerve crush,9 polyglutamine disease,9,10 autoimmune uveitis,11,12 and retinal detachment 13. Moreover, inhibition of Hsp90 has neuroprotective effects in inherited retinal degeneration and polyglutamine diseases at least partially mediated by HSF1 14,15.…”
mentioning
confidence: 99%